Sport against the threats of the modern world - Jolanta Elżbieta Kowalska (Journal of Education, Health and Sport, 2018)
The study points out the problem of sports threats in the face of threats in the modern world, ie commercialization, dehumanization, doping, aggression of the sports audience, and what is connected with this attempt to win by athletes at all costs. The author, pointing to these problems, presents them in the context of respecting the principle of fair in sport as an opportunity to preserve its educational values.